The Role of Pujakesuma Organization in Include Human Values to Improve Social Justice in Teladan Barat Village - Dewi Romantika Tambunan; Nazlah Aulia; Marly Meani Silalahi; Putri Widia Ningsih; Jamaludin Jamaludin (International Journal of Social Welfare and Family Law, 2024)
This study explores the role of the Pujakesuma organization in instilling humanitarian values and improving social justice in Teladan Barat Village through the Warung Nusantara program. The community in this area, which is mostly from the lower middle class, faces challenges in meeting basic needs due to inflation and price fluctuations. Through Warung Nusantara, Pujakesuma provides basic necessities at affordable prices, helps the underprivileged and strengthens social solidarity. The research method used is qualitative descriptive, with data collection through observation, interviews, and documentation. The results of the study show that this program not only provides access to basic needs, but also educates the community about caring and solidarity. In addition, Pujakesuma serves as a role model for other organizations in improving social justice. However, the main challenge is gathering members who are willing to contribute voluntarily. This study is expected to provide insights for stakeholders to develop similar initiatives that are more effective.